Disease severity and genetic pathways in attenuated familial adenomatous polyposis vary greatly but depend on the site of the germline mutation. Issue 10 (4th February 2006) - Sieber, O M; Segditsas, S; Knudsen, A L; Zhang, J; Luz, J; Rowan, A J; Spain, S L; Thirlwell, C; Howarth, K M; Jaeger, E E M; Robinson, J; Volikos, E; et al.
Abstract : Background: Attenuated familial adenomatous polyposis (AFAP) is associated with germline mutations in the 5′, 3′, and exon 9 of the adenomatous polyposis coli ( APC ) gene. These mutations probably encode a limited amount of functional APC protein. Methods and results: We found that colonic polyp number varied greatly among AFAP patients but members of the same family tended to have more similar disease severity. 5′ Mutants generally had more polyps than other patients. We analysed somatic APC mutations/loss of heterozygosity (LOH) in 235 tumours from 35 patients (16 families) with a variety of AFAP associated germline mutations. In common with two previous studies of individual kindreds, we found biallelic changes ("third hits") in some polyps. We found that the "third hit" probably initiated tumorigenesis. Somatic mutation spectra were similar in 5′ and 3′ mutant patients, often resembling classical FAP. In exon 9 mutants, in contrast, "third hits" were more common. Most "third hits" left three 20 amino acid repeats (20AARs) on the germline mutant APC allele, with LOH (or proximal somatic mutation) of the wild-type allele; but some polyps had loss of the germline mutant with mutation leaving one 20AAR on the wild-type allele. Conclusions: We propose that mutations, such as nt4661insA, that leave three 20AARs are preferentially selected in cis with some AFAP mutations because the residual protein function is near optimal for tumorigenesis. Not all AFAP polyps appear to need "three hits" however. AFAP is phenotypically and genetically heterogeneous. In addition to effects of different germline mutations, modifier genes may be acting on the AFAP phenotype, perhaps influencing the quantity of functional protein produced by the germline mutant allele.